Development Of E-LKPD hots questions as a medium for learning mathematics on the material of the Phytagorean theorem - Nuraisyah, Nuraisyah; Pasaribu, Laili Habibah; Julyanti, Eva (Universitas Islam Negeri Raden Intan Lampung, 2024)
Learning in the modern era demands learning based on KBAT, literacy skills, character education, and 4C (critical, creative, collaborative, and collaborative), all of which can be achieved through the development of E-LKPD based on KBAT combined with critical thinking skills indicators. The purpose of this study is to produce an E-LKPD product using KBAT-based questions, to determine whether the KBAT-based E-LKPD is suitable for the material of the Pythagoras theorem, and to determine the student's reaction to the created KBAT-based E-LKPD. . This refers to the ADDIE model. This study involves eighth grade students of SMP N 2 Utara Province who are the subject of this study and the object of this study is E-LKPD using KBAT based questions. Student questionnaires and confirmation sheets were used in this study. This study obtained the results which are: (1) The feasibility of E-LKPD using KBAT-based questions by media experts is in the feasible category (80.00) and material experts are also in the feasible category (77.5); and (2) Student response to E-LKPD using KBAT-based questions is in the good category with an average of 81.1%. Thus, this study shows that E-LKPD using KBAT-based questions can be used as media in the learning and teaching process.